2009
DOI: 10.1590/s0102-33062009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Arquitetura foliar comparativa de Miconia sellowiana (DC.) Naudin (Melastomataceae) em diferentes fitofisionomias no Estado do Paraná, Brasil

Abstract: RESUMO -(Arquitetura foliar comparativa de Miconia sellowiana (DC.) Naudin (Melastomataceae) em diferentes fitofisionomias no Estado do Paraná, Brasil). Estudos prévios sobre M. sellowiana, em quatro fitofisionomias no Estado do Paraná, Brasil, mostraram que suas folhas apresentaram uma grande plasticidade morfológica. Este trabalho objetivou dar continuidade ao estudo sobre a plasticidade da espécie, utilizando como indicadores as seguintes características foliares: área e massa, massa específica, espessura, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…The leaf vein system may vary in response to the environmental conditions of the different biomes. (Boeger et al 2009, Sack & Scoffoni 2013. Despite this, the leaf venation pattern is an important character used for taxonomic distinction (Ellis et al 2009, Borrero et al 2016, Coutinho 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf vein system may vary in response to the environmental conditions of the different biomes. (Boeger et al 2009, Sack & Scoffoni 2013. Despite this, the leaf venation pattern is an important character used for taxonomic distinction (Ellis et al 2009, Borrero et al 2016, Coutinho 2016.…”
Section: Discussionmentioning
confidence: 99%
“…(Souza & Amaral, 2015), Psidium cattleianum and Psychotria suterella (Moraes et al, 2013); but some studies found lower coefficient of determination for the relation between leaf and L × W for the species Crotalaria juncea L. (Cardozo et al, 2014). The results show the efficiency of the model with the product of the length and width as the predictor variable for the determination of leaf area, which may be related to a higher amount of information provided through the two dimensions (Boeger et al, 2009;Monteiro et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…According to Cornelissen et al (2003), low values of SLA indicate that plants are investing more in structural components, which increase their resistance against desiccation and herbivory and, in the case of the present study, against frosting. Boeger et al (2009), when studying leaves of Miconia sellowiana (DC.) Naudim in communities at different stages of succession in Paraná State, Brazil, verified that in the early succession stage leaves are usually thicker and with smaller specific leaf area -a pattern similar to that found in this study.…”
Section: Discussionmentioning
confidence: 99%